Temporary Anchorage Devices in the Management of Malocclusion in Pediatric Patients: Scoping Review - Tiffany Yuliarti Pelawi; Prima Andisetyanto (SONDE (Sound of Dentistry), 2026)
Introduction: Malocclusion is a prevalent developmental disorder in children that negatively impacts dental function, aesthetics, and craniofacial growth. Temporary Anchorage Devices (TADs) have been introduced as an alternative to conventional anchorage methods in pediatric orthodontics, aiming to overcome challenges such as inadequate anchorage and poor patient compliance. Methods: This scoping review was conducted to systematically investigate the clinical application, effectiveness, and outcomes of TADs in managing malocclusion among pediatric patients. Literature searches were performed in PubMed, Scopus, and EBSCOhost for studies published from 2014 to 2024 in accordance with PRISMA-ScR guidelines. Inclusion criteria were human studies focusing on pediatric patients treated with TADs; studies on animals, non-English languages, or published before 2014 were excluded. Study selection followed the Population, Concept, and Context (PCC) framework, and quality assessment was conducted using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. Results and Discussion: A total of 7 studies met the criteria, including cohort studies, case series, case reports, and one randomized controlled trial. Most studies demonstrated that TADs provide absolute anchorage, increase flexibility in tooth movement, and reduce dependence on patient cooperation in complex cases. Conclusion: In conclusion, TADs represent a significant advancement in pediatric orthodontic care, enabling more predictable and effective management of malocclusion. Keywords: Temporary Anchorage Devices, Pediatric Orthodontics, Malocclusion, Miniscrew